Methodology for Forming Calculation Skills in Pupils of Primary Class Through Interactive Methods - Kasimov Fayzullo Muxamedovich; Usmonova Zulfiya Ilxomovna (Zien Journals, 2023)
This article discusses the content and essence of using interactive methods in the formation of computing skills in elementary school students.
Keywords: interactive method; primary education; computing skills; thought